Serum L‐arginine and endogenous methylarginine concentrations predict irritable bowel syndrome in adults: A nested case‐control study. Issue 7 (25th August 2021) - McEvoy, Mark A.; Attia, John R.; Oldmeadow, Christopher; Holliday, Elizabeth; Smith, Wayne T.; Mangoni, Arduino A.; Peel, Roseanne; Hancock, Stephen J.; Walker, Marjorie M.; Talley, Nicholas J.
Abstract: Background & Aims: Nitric oxide, a major inhibitory nonadrenergic, noncholinergic neurotransmitter that relaxes smooth muscle, may be implicated in the pathophysiology of visceral hypersensitivity in irritable bowel syndrome (IBS). Impaired bioavailability of the nitric oxide precursor molecule L‐arginine and higher concentrations of methylarginines (endogenous inhibitors of nitric oxide synthesis) are known to impair nitric oxide synthesis in numerous gastrointestinal cell types. We therefore examined serum concentrations of L‐arginine and the methylarginines in a nested case‐control study, to assess whether these factors are associated with adult IBS. Methods: Data on clinical characteristics, methylarginines, and L‐arginine (measured using LC‐MS/MS) were collected from a random population‐based cohort of Australian adults (median age = 64 years; IQR = 60–70). Cases of IBS, defined according to Rome III criteria ( N  = 156), and controls ( N  = 332) were identified from within the cohort at the 5‐year follow‐up. Results: In adjusted logistic regression analyses, L‐arginine, asymmetric dimethylarginine, symmetric dimethylarginine, L‐arginine/asymmetric dimethylarginine ratio, and Kessler‐10 psychological distress scores were significantly associated with IBS ( p  < 0.05). [Correction added on 18 September 2021, after first online publication: In the preceding sentence, the value ( p  > 0.05) has been changed to ( p  < 0.05)]. Similar results were found for IBS subtypes. Higher serum L‐arginine concentration had the strongest association with IBS diagnosis, with an odds ratio of 9.03 for those with serum L‐arginine at the 75th (84 μmol/L) versus 25th (46 μmol/L) percentile (95% CI: 5.99–13.62). L‐arginine had the best discriminative ability with a bias‐adjusted area under the receiver operator characteristic curve of 0.859. Conclusions: Higher serum concentrations of L‐arginine and endogenous methylarginines are strongly associated with IBS in adults.